Evaluation of the Effect of Maribavir on Cardiac Repolarization in Healthy Participants: Thorough QT/QTc Study. Issue 6 (4th July 2020) - Ilic, Katarina; Song, Ivy; Wu, Jingyang; Martin, Patrick
Abstract : Maribavir is an orally bioavailable benzimidazole riboside in clinical development for treatment of cytomegalovirus infection in patients who undergo transplantation. Maribavir was evaluated in a thorough QT (TQT) study to determine any effects on cardiac repolarization. The effect of maribavir 100 and 1, 200 mg oral doses on the baseline‐adjusted and placebo‐adjusted corrected QT (QTc) interval (delta delta QTc (ddQTc)) and other electrocardiogram (ECG) parameters was assessed in a randomized, phase I, placebo‐controlled, four‐period crossover study in healthy participants (men and women ages 18–50 years). Additionally, maribavir pharmacokinetics, safety, and tolerability were investigated. Moxifloxacin (400 mg) was used as a positive control to demonstrate the study's ability to detect QT prolongation. Digital 12‐lead Holter ECG monitoring was performed over 22 hours following study drug administration. Individual, Fridericia's, and Bazett's QTc intervals were calculated. Of 52 randomized participants (29 ± 8.1 years old; 31 men (60%)), 50 (96%) completed the study. For both 100‐mg and 1200‐mg doses of maribavir, analysis of ddQTc demonstrated that the upper bound of the two‐sided 90% confidence interval was below the 10‐ms threshold at all time points. The concentration–effect analysis demonstrated no relationship between ddQTc and plasma concentrations of maribavir (and its metabolite). There were no clinically meaningful changes in heart rate and systolic blood pressure. The most common adverse event was dysgeusia; no serious adverse events were reported. This TQT study demonstrated that maribavir did not have impact on cardiac repolarization.